MENINGKATKAN PEMAHAMAN KONSEP PERSAMAAN KUADRAT MELALUI MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) UNTUK SISWA KELAS X - Wulandari, Bella; Ratumanan, Tanwey Gerson; Ngilawajan, Darma Andreas (Program Studi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Pattimura, 2023)
Abstract IMPROVING UNDERSTANDING OF THE CONCEPT OF QUADRATIC EQUATIONS THROUGH THINK PAIR SHARE (TPS) LEARNING MODEL FOR CLASS X STUDENTS OF SMAN 13 AMBON This study aims to improve the understanding of the concept of quadratic equations by applying the Think Pair Share (TPS) learning model in class X students of SMAN 13 Ambon. The type of research used was classroom action research with data collection techniques through concept understanding tests. the subjects in this study were 30 students of class X SMAN 13 Ambon. The results showed that by using the Think Pair Share (TPS) learning model can improve the understanding of the concept of quadratic equations of class X students of SMAN 13 Ambon. The average percentage of concept understanding from cycle I to cycle III is 63%; 70%; 82% with moderate, high, high categories respectively. The average percentage of achievement of each indicator of concept understanding is; (1) restate a concept: 54%;66%;93%. (2) using and selecting certain procedures or operations: 57%;66%68%. (3) applying concepts or algorithms in problem solving: 78%;79%;82%. The percentage of student learning completeness from cycle I to cycle III was 39.13%; 56.52%; 82.60% respectively.